Neonatal Outcomes of Late-Preterm Birth Associated or Not with Intrauterine Growth Restriction - Cristiane Ortigosa Rocha; Roberto Eduardo Bittar; Marcelo Zugaib (Hindawi Limited, 2010)
Objective. To compare neonatal morbidity and mortality between late-preterm intrauterine growth-restricted (IUGR) and appropriate-for-gestational-age (AGA) infants of the comparable gestational ages (GAs). Methods. We retrospectively analyzed neonatal morbidity and mortality of 50 singleton pregnancies involving fetuses with IUGR delivered between 34 and 36 6/7 weeks of GA due to maternal and/or fetal indication. The control group consisted of 36 singleton pregnancies with spontaneous preterm delivery at the same GA, in which the infant was AGA. Categorical data were compared between IUGR and AGA pregnancies by 𝑋2 analysis and Fisher's exact test. Ordinal measures were compared using the Kruskal-Wallis test. Results. The length of stay of newborns in the nursery, as well as the need for and duration of hospitalization in the neonatal intensive care unit, was longer in the group with IUGR. Transient tachypnea of the newborn or apnea rates did not differ significantly between the IUGR and AGA groups. IUGR infants were found to be at a higher risk of intraventricular hemorrhage. No respiratory distress syndrome, pulmonary hemorrhage or bronchopulmonary dysplasia was observed in either group. The frequency of sepsis, thrombocytopenia and hyperbilirubinemia was similar in the two groups. Hypoglycemia was more frequent in the IUGR group. No neonatal death was observed. Conclusion. Our study showed that late-preterm IUGR infants present a significantly higher risk of neonatal complications when compared to late-preterm AGA infants.